2015
DOI: 10.3126/ijls.v9i6.11585
|View full text |Cite
|
Sign up to set email alerts
|

RNA: DNA Ratio and Growth Performance of Rohu Labeo rohita (Hamilton) Fed Varied Proportion of Protein Diet during Intensive Aquaculture

Abstract: An experiment was conducted at Corona of Agriculture (COA)”, Gunjanagar-3, Chitwan, Nepal to complete a project granted by University Grant Commission (UGC), Second Higher Education Project (SHEP) in 2013. Four (average 380 m2) ponds (W, X, Y and Z) with four different diets as D1 (20%), D2 (30%), D3 (40%) and D4 (50%) protein contents were used to conduct the experiment properly to determine the varied proportion of dietary protein on the growth performance of major carp rohu Labeo Rohita (H) in relation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The present value of ratio ranged from 0.834±0.08 to 1.609±0.017 which falls in the expected range i.e., the lowest is for the control and highest for the higher % of silkworm pupae fed diet. The ratio was found to be high in the treatment having 50% protein compared to the treatments having a protein level below this and followed the increasing trend as the protein level was increased (Labh, 2015). Comparing these results to our findings a similar trend was followed with the highest in the treatment in which more concentration of silkworm pupae was fed followed by a decreasing trend in the rest of the treatments.…”
Section: Rna:dna Ratiosupporting
confidence: 82%
“…The present value of ratio ranged from 0.834±0.08 to 1.609±0.017 which falls in the expected range i.e., the lowest is for the control and highest for the higher % of silkworm pupae fed diet. The ratio was found to be high in the treatment having 50% protein compared to the treatments having a protein level below this and followed the increasing trend as the protein level was increased (Labh, 2015). Comparing these results to our findings a similar trend was followed with the highest in the treatment in which more concentration of silkworm pupae was fed followed by a decreasing trend in the rest of the treatments.…”
Section: Rna:dna Ratiosupporting
confidence: 82%
“…Both the control and test ponds (for both the size classes) were stocked with IMC (N=300), namely rohu (Labeo rohita), catla (Labeo catla), and mrigal (Cirrhinus mrigala), following a standard ratio of 1:3:1 (Debnath et al, 2020). We stocked rohu more in the ponds as it has relatively higher economic value when compared to other two carps (Labh et al, 2014). Moreover, in most aquatic ecosystems, rohu acts as a keystone species (Dwivedi et al, 2020).…”
Section: Study Site and Mesocosm Setupmentioning
confidence: 99%
“…A higher RNA: DNA ratio was recorded in T3 (35% CSM protein) diet fed fish compared to control and other treatments. Labh (2015) reported that DNA / RNA ratios were increased rapidly with age and sizes of fishes.…”
Section: Dna / Rna Ratiomentioning
confidence: 99%